Cumulative Live Birth Rates After the First ART Cycle Using Flexible GnRH Antagonist Protocol vs. Standard Long GnRH Agonist Protocol: A Retrospective Cohort Study in Women of Different Ages and Various Ovarian Reserve - Zhang, Wanlin; Xie, Duo; Zhang, Hengde; Huang, Jianlei; Xiao, Xifeng; Wang, Binrong; Tong, Yafei; Miao, Ye; Wang, Xiaohong (Frontiers in Endocrinology, 2020)
Objective:To compare the cumulative live birth rates (cLBRs) after the first assisted reproductive technology (ART) cycle using flexible gonadotropin releasing hormone (GnRH)-antagonist protocol versus standard long GnRH agonist protocol for controlled ovarian stimulation (COS) in infertile women with different ages and ovarian reserve. Methods: Women who underwent ART treatment at our center between June 1st, 2015 and December 31st, 2018 were screened. Among them, only women who underwent their first COS cycle with flexible GnRH antagonist protocol or standard long GnRH agonist protocol were included in this study.The main outcome measurement was cLBR. Results:A total of 4,402 patients were eligible for the analysis, of whom, 2,762 patients used the GnRH agonist protocol and 1,640 patients used the GnRH antagonist protocol. The cLBRs of women in the antagonist protocol group and long agonist protocol group were 45.3% and 50.0%, respectively. Subgroup multivariable regression analysis showed that, in patients with low ovarian reserve (AFC<=7), the cLBR was significantly lower in the antagonist group than in the long agonist protocol group [OR (95% CI) 0.62 (0.41, 0.94)], which effect was more robust in younger patients (< 30 y) [OR (95% CI) 0.29 (0.11, 0.74)]. The analysis also revealed remarkably lower cLBR in patients above 40 years regardless of their AFC, although the difference was not statistically significant. However, in patients with high ovarian reserve (AFC >24), the cLBR was higher in cycles with antagonist protocol than with the long agonist protocol [OR (95% CI) 1.43 (0.96, 2.12)], and the effect was of statistical significance in younger patients (< 30 y) [OR (95% CI) 1.78 (1.07, 2.96)]. Conclusion:The present study suggests that the flexible GnRH antagonist protocol might not be suitable for patients with low ovarian reserve (AFC <=7) or patients aged over 40 years. However, flexible GnRH antagonist protocol might be strongly recommended for patients under 30 years old and with high ovarian reserve (AFC >24). For the rest groups of patients in the present cohort, antagonist protocol was slightly favored because it had lower OHSS in general and in patients with poly-cystic ovarian syndrome (PCOS) according to previous publications.